Effect of polishing methods on Candida albicans adhesion and contributing factors in heat-cured acrylic dentures: an in-vitro comparative study - Shahrukh Ali Khan; Zulfiqar Ali Mirani; Taimur Khalid; Engr Muhammad Wasiq Ali Khan; Ziaullah Choudhary; Syed Murtaza Raza Kazmi (BMC Oral Health)
Abstract Introduction Heat-polymerized acrylic resin is widely used in prosthodontics due to its various advantages. However, its susceptibility to microbial colonization, influenced by surface properties such as roughness, water sorption, and free surface energy, poses challenges in maintaining oral health. Microbial adhesion, particularly of Candida albicans, plays a significant role in the overall microbial load on the denture surface, predisposing several oral and health related complications. While polishing techniques improve surface smoothness, their effects on water sorption and free surface energy, which are critical to microbial adhesion, remain understudied. This study explores the impact of Mechanical Polishing (MP) and Chemical Polishing (CP) methods on these surface properties and their potential to reduce Candida albicans adhesion. Materials and Methods Twenty-four square samples of heat-cured acrylic were fabricated and divided into two groups of 12 for MP and CP respectively. Surface roughness (Ra) was measured using a profilometer. Scanning Electron Microscopy (SEM) analysis was conducted on polished and unpolished specimens. Water sorption was assessed through weekly weighing, and free surface energy was determined using a goniometer. Candida albicans identification was done using Dichloran Rose-Bengal Chloramphenicol (DRBC) agar and confirmation was achieved through microscopy and growth on selective media. Adherence and viable assays were performed on both polished and non-polished specimens. Statistical analysis was performed using SPSS (Version 24.0). Mann-Whitney U test compared surface roughness, water sorption, free surface energy, and initial adherence between MP and CP groups. Linear regression analysis examined the influence of these factors on Candida albicans adherence. Results Surface roughness did not significantly differ between the two polishing methods. However, CP resulted in significantly reduced water sorption, lower free surface energy, and decreased Candida albicans adhesion compared to MP. A significant negative association was observed between CP and Candida adherence. Conclusion Both polishing methods achieved the desired level of surface smoothness. However, CP demonstrated superior performance in reducing water sorption, free surface energy, and Candida albicans adhesion. This suggests its practical benefits in clinical settings, particularly intaglio surfaces where MP is impractical.